Plano de projeto: desenvolvimento e implantação de escritório de projetos em uma empresa do ramo varejista de presentes e decoração. - Schein, Catarina Madrid da Silveira (Universidade do Vale do Rio dos Sinos, 2018)
This final paper has the development of a project plan to the full implementation of a Project Office in a gifts and decoration company as its main goal. In order to achieve that goal, plans for integration, scope, time, costs, quality, resources, communication, risks, acquisitions and stakeholders were developed. As the needs to execute and manage the project were defined and, based on the good practices contained in the PMBOK Guide (Project Management System of Knowledge) 6th edition, the project plan was elaborated regarding all of those topics.
Keywords: Gestão de Projetos; Escritório de Projetos; Definição de escopo; Project Management; Project Office; Scope definition